ANALISIS IMPLEMENTASI GERAKAN LITERASI SEKOLAH - Maulida, Ikrima; Lestari, Eci Anita; Sari, Cut Kumala (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
In this modern era, literacy mastery is very crucial for students. To develop literacy competencies in learning, a fundamental step is to cultivate the habit of reading. Gerakan Literasi Sekolah (GLS) program was formed in 2015 and began to be implemented nationally in all educational institutions in Indonesia since 2016, as a response to the low level of literacy in the Indonesian people. Therefore, this article discusses the analysis of the implementation of the school literacy movement. This study uses a qualitative approach and a descriptive narrative research type. This research was conducted at SD Negeri 2 Percontohan Blangkejeren, Blangkejeren District, Gayo Lues Regency. The data sources came from informants consisting of grade I to VI teachers. The data collection methods used were semi-structured interviews, observation and documentation. The data analysis method used the Milles and Huberman Model data analysis technique consisting of data condensation, data presentation, and conclusions. While the data validity test used data triangulation techniques, namely triangulation of sources and techniques. Based on the results of the data analysis, it can be concluded that the implementation of the GLS program has brought great benefits to all school residents. Students are not only trained to read, but also developed in terms of self-confidence, insight, and creativity, including in utilizing used goods into works. Thus, GLS is able to create an active, creative, and literate learning environment. ABSTRAK Di era modern ini, penguasaan literasi sangat krusial bagi siswa. Untuk mengembangkan kompetensi literasi dalam pembelajaran, langkah fundamental adalah membudayakan kebiasaan membaca. Program Gerakan Literasi Sekolah (GLS) dibentuk pada tahun 2015 dan mulai diterapkan secara nasional di seluruh lembaga pendidikan di Indonesia sejak tahun 2016, sebagai respons terhadap rendahnya tingkat literasi masyarakat Indonesia. Oleh karena itu, artikel ini membahas mengenai analisis implementasi gerakan literasi sekolah. Penelitian ini menggunakan pendekatan kualitatif dan jenis penelitian deskriptif naratif. Penelitian ini dilaksanakan di SD Negeri 2 Percontohan Blangkejeren Kecamatan Blangkejeren Kabupaten Gayo Lues. Sumber data berasal dari informan yang terdiri dari guru kelas I sampai VI. Metode pengumpulan data yang digunakan adalah wawancara semi terstruktur, observasi dan dokumentasi. Metode analisis data menggunakan teknik analisis data Model Milles dan Huberman yang terdiri atas, Kondensasi data, penyajian data, dan penarikan kesimpulan. Adapun uji keabsahan data menggunakan teknik triangulasi data yaitu triangulasi sumber dan teknik. Berdasarkan hasil analisis data dapat disimpulkan bahwa , implementasi program GLS telah membawa manfaat besar bagi seluruh warga sekolah. Siswa tidak hanya dilatih untuk membaca, tetapi juga dikembangkan dari segi kepercayaan diri, wawasan, dan kreativitas, termasuk dalam memanfaatkan barang bekas menjadi karya. Dengan demikian, GLS mampu menciptakan lingkungan belajar yang aktif, kreatif, dan literatif.